2021
DOI: 10.1186/s13033-021-00464-0
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime relapse and its associated factors among people with schizophrenia spectrum disorders who are on follow up at Comprehensive Specialized Hospitals in Amhara region, Ethiopia: a cross-sectional study

Abstract: Background Relapse in psychiatric disorders is highly distressing that posed a huge burden to the patients, family, and society. It interrupts the process of recovery and may increase the risk of resistance to treatment. Relapse detection and taking preventive measures against its possible factors are crucial for a better prognosis. Objective To assess lifetime relapse and its associated factors among people with schizophrenia spectrum disorders wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 58 publications
1
13
0
1
Order By: Relevance
“…A qualitative study's systematic review on the experience of patients with LAIs showed that patients' education is essential, as well as a close therapeutic context with the attending physician, to increase patient adherence to such therapeutics (19). In the cases where this happens, the overall subjective experience of patients is deemed as very positive (9)(10)(11)18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A qualitative study's systematic review on the experience of patients with LAIs showed that patients' education is essential, as well as a close therapeutic context with the attending physician, to increase patient adherence to such therapeutics (19). In the cases where this happens, the overall subjective experience of patients is deemed as very positive (9)(10)(11)18).…”
Section: Introductionmentioning
confidence: 99%
“…This condition is characterized by multiple relapses and psychotic episodes which have a significant detrimental impact on the life of patients and their families—impacting the performance in work and/or academic-related tasks ( 5 , 6 ) and quality of life ( 7 , 8 ). Relapses are common in schizophrenia, especially during the first years of treatment ( 9 – 11 ). Also, schizophrenia can pose a significant strain on public healthcare services, as a result of a high rate of hospitalizations and indirect costs ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Menurut asumsi peneliti, usia dapat menjadi faktor utama kekambuhan, hal tersebut muncul karena perilaku kesehatan yang terbentuk seiring bertambahnya usia akan memengaruhi kepatuhan seseorang dalam pengobatan. Hal ini konsisten dengan hasil penelitian lain yang menunjukkan bahwa ketidakpatuhan pengobatan memiliki resiko lebih dari dua kali lipat mengalami kekambuhan dari pada yang patuh pada pengobatan (Moges, et al, 2021). Selain itu, pada usia dewasa kekambuhan dapat berulang apabila tidak didukung dengan support system terutama lingkungan keluarga, dimana kontrol minum obat memiliki pengaruh besar pada kepatuhan dan kekambuhan berulang.…”
Section: Pembahasan Hubungan Usia Dengan Kekambuhan Pada Pasien Skizo...unclassified
“…Of those who are hospitalized, ∼30-50% experience a relapse of symptoms within the first 6 months and 50-70% in the first 5 years after being discharged (Chang and Chou, 2015;Ali et al, 2017;Sadock et al, 2017). Comorbidity with other mental illness, non-adherence to medication, shorter duration on treatment and experiencing stressful life events as well as high disability score, and a single admission history are significant predictors of mental health relapse (Agenagnew and Kassaw, 2020;Moges et al, 2021). Patients with psychotic disorders who also experience common mental health disorders such as depression and anxiety are more likely to experience a relapse (Ali et al, 2017;Moges et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Comorbidity with other mental illness, non-adherence to medication, shorter duration on treatment and experiencing stressful life events as well as high disability score, and a single admission history are significant predictors of mental health relapse (Agenagnew and Kassaw, 2020;Moges et al, 2021). Patients with psychotic disorders who also experience common mental health disorders such as depression and anxiety are more likely to experience a relapse (Ali et al, 2017;Moges et al, 2021). Some novel approaches such as receiving low-intensity personalized advice via text-messages post-treatment (Malins et al, 2020) and specific forms of therapy such as Acceptance and Commitment Therapy (Østergaard, 2020), mind-body relaxation and therapies that allow the patient to develop healthy coping skills (Melemis, 2015) can be particularly beneficial in relapse prevention.…”
Section: Introductionmentioning
confidence: 99%